Investigation of a wool measurement device for determining the mean diameter of a sample consisting of multiple wool fibres - Spangenberg, Dirk-Mathys (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--Stellenbosch University, 2012.